Exploring transitional justice as a vehicle for social and political transformation in Kenya - Asaala, Evelyne Owiye (University of Pretoria, 2010)
Dissertation submitted to the Faculty of Law University of Pretoria, in partial fulfilment of the requirements for the degree Masters of Law (LLM in Human Rights and Democratisation in Africa). Prepared under the supervision of Dr. Atangcho N Akonumbo, Faculte de Sciences Sociales et de Gestion Universite Catholique D’Afrique Centrale Yaounde Cameroun.